THE EFFECT OF GUESS GAME TO IMPROVE STUDENT - Elysa Rohayani Hasibuan (JURNAL EDUSCIENCE (JES), 2018)
This study aims to determine speaking ability of students in MAN Rantauprapat using a guess game. Data collection technique used in this research is direct observation and test. In this study population is entire amount to 60 students in two class. Data analysis technique used in this study is a technique Product Moment Correlation. The normal data distributive with using aplication software SPSS versi 22. This research use a instrument to collecting the data is a test in multiple choice, there are 25 test with 5 option. (a, b, c, d and e). The result Pre-test in experiment class is 38,2 and at control class is 32.2. Wheares at Pot- Test in experiment class is 72.66 and the control class is 64.13. hypothesis testing can get t-hitung = 3.81 and t-table = 2.04 (t-hitung > t- table) at = 0.05 it show that H0 is rejected and Ha is accepted. This is show that